Research ethics: From principles to practical aspects - Gonzalo Solis Sánchez; Guillermo Alcalde Bezhold; Iciar Alfonso Farnós (Elsevier, 2023)
Any research conducted on human beings or human biological samples requires a prior ethical assessment to avoid risks and problems for all involved parties. The legislation in this regard is very broad and emphasizes the safeguarding of patient rights in relation to the universal principles of autonomy, beneficence and justice. The present article reviews the regulations applicable to clinical trials, observational studies with drugs, biobank projects or any other type of study that may be conducted in the health care field. It also addresses the role of research ethics committees, data protection and the foundations of scientific integrity. Resumen: La realización de cualquier investigación con seres humanos o sus muestras biológicas requiere una valoración ética previa con el fin de evitar riesgos y problemas a todos los actores del proceso. La legislación al respecto es muy amplia y hace hincapié en la preservación de los derechos de los pacientes en relación con los principios universales de autonomía, beneficencia y justicia. En este manuscrito se revisan las normativas sobre ensayos clínicos, estudios observacionales con medicamentos, proyectos de biobanco o cualquier otro tipo de estudio que se pueda realizar en el ámbito de la salud. Así mismo se analiza el papel de los comités de ética en Investigación, la protección de datos y las bases de la integridad científica.